2023
DOI: 10.3389/fimmu.2023.1105420
|View full text |Cite
|
Sign up to set email alerts
|

Designing neoantigen cancer vaccines, trials, and outcomes

Abstract: Neoantigen vaccines are based on epitopes of antigenic parts of mutant proteins expressed in cancer cells. These highly immunogenic antigens may trigger the immune system to combat cancer cells. Improvements in sequencing technology and computational tools have resulted in several clinical trials of neoantigen vaccines on cancer patients. In this review, we have looked into the design of the vaccines which are undergoing several clinical trials. We have discussed the criteria, processes, and challenges associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 100 publications
0
18
0
Order By: Relevance
“…Advances in NGS technologies and bioinformatic tools have enabled the identification of mutations and prediction of mutation-derived neoAgs, allowing the development of different therapeutic strategies focused on neoAgs as targets. 30 , 31 For this purpose, different algorithms have been developed and are currently applied. Briefly, neoAg identification requires first whole genome/exome sequencing of tumor and healthy tissue, alignment to a reference genome and, after eliminating germline polymorphisms, identification of mutations by using variant caller tools (e.g.…”
Section: Neoantigens Originated From Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in NGS technologies and bioinformatic tools have enabled the identification of mutations and prediction of mutation-derived neoAgs, allowing the development of different therapeutic strategies focused on neoAgs as targets. 30 , 31 For this purpose, different algorithms have been developed and are currently applied. Briefly, neoAg identification requires first whole genome/exome sequencing of tumor and healthy tissue, alignment to a reference genome and, after eliminating germline polymorphisms, identification of mutations by using variant caller tools (e.g.…”
Section: Neoantigens Originated From Mutationsmentioning
confidence: 99%
“… 42 Finally, if available and as an additional filter for neoAg identification, gene expression obtained by RNASeq can be used to identify those putatively expressed neoAgs. 30 In this respect, it has been recently reported that many published mutated neoAgs are also expressed (at the RNA level) in normal tissues and cannot be considered as true neoantigens, suggesting the need of using adequate tools to identify tumor-specific neoAgs. 43 Overall, this strategy bears important limitations, such as the suboptimal prediction capacity of some algorithms (e.g.…”
Section: Neoantigens Originated From Mutationsmentioning
confidence: 99%
“…In cancer vaccine practice, a tumor cell sample is gathered and the somatic mutations from the whole genome or exome are identified. From there, experiments and algorithms help to identify the most suitable ‘neopeptides’, and the appropriate DNA sequences are loaded in to a viral vector or the gene is loaded in to a plasmid to be injected into the patient [ 101 ]. This is the framework in which ‘personalized’ DNA vaccines [ 102 ] are presented and the idea behind anti-tumor vaccines [ 96 , 97 , 103 ], many of which are currently in clinical trial [ 104 ].…”
Section: Designmentioning
confidence: 99%
“…The sources of tumour antigens mainly include TAA and TSA 155,156 . TAA, such as CEA, is not an optimal target for immunotherapy.…”
Section: The Challenge Of Neoantigen‐based Therapy In Crcmentioning
confidence: 99%
“…154 The sources of tumour antigens mainly include TAA and TSA. 155,156 TAA, such as CEA, is not an optimal target for immunotherapy. First, because TAA is also expressed in some normal tissues, immunotherapy against TAA may activate the immune response in non-target tissues and cause severe autoimmune toxicity, such as severe hepatitis, colitis, rapid respiratory failure, renal insufficiency and even death.…”
Section: The Challenge Of Neoantigen-based Therapy In Crcmentioning
confidence: 99%